Prevalence and incidence of type 1 diabetes in children aged 0–14 years old in New Zealand in 2021. (28th January 2023) - Wu, Rachel; Burnside, Mercedes; Davies, Hannah; Jefferies, Craig; Wheeler, Benjamin; Paul, Ryan; Wiltshire, Esko; de Bock, Martin; Williman, Jonathan
Abstract : Aim: National prevalence and incidence data are important for understanding population trends and allocating health‐care resources. We aimed to provide a current national snapshot of prevalence and annual incidence rates for children aged 0–14 with type 1 diabetes (T1D) in Aotearoa New Zealand and to identify differences associated with demographic variables. Methods: Paediatric diabetes centres across Aotearoa were invited to record anonymised demographic and diabetes data on children under their services between 1 October 2020 and 30 September 2021. National prevalence and incidence were calculated using usually resident population counts from the 2018 census. The effect of ethnicity on prevalence and incidence was assessed using Poisson regression. Results: There were 1209 children aged 0–14 with T1D in October 2021. The national prevalence was 131/100 000 (95% confidence interval (CI) 124–139). European children had twice the prevalence as those of Māori or Pacific ethnicity ( P  < 0.001). There was no effect by gender ( P  = 0.3) and prevalence predictably increased with age. The annualised incidence of T1D was 23/100 000 (95% CI 20–26). European children were 2.6 times as likely as Māori children to be diagnosed with T1D in that year (incidence rate ratio = 2.6, 95% CI 1.7–4.2). Regional differences in prevalence and incidence were noted, potentially due to the ethnicity differences across regions. Unadjusted prevalence and incidence decreased with lower socio‐economic status, likely due to an over‐representation of non‐Europeans living in the most deprived areas. Conclusions: T1D affects an ethnically diverse population in Aotearoa and important regional differences exist that may impact workforce planning.